A Political Companion to James Baldwin (University Press of Kentucky, 2017)
"Acclaimed author and social critic James Baldwin (1924-1987) maintained that all American literature is intrinsically bound to the nation's social history and that all American writers are products of its political system. In seminal works such as Go Tell It on the Mountain, Notes of a Native Son, and The Fire Next Time, he expresses his profound belief that writers have the power to transform society, to engage the public, and to inspire and channel conversation to achieve lasting change. While Baldwin is best known for his writings on racial consciousness and injustice, he is also one of the country's most eloquent theorists of democratic life and the national psyche. In A Political Companion to James Baldwin, a group of prominent scholars assess the prolific author's relevance to present-day political challenges. Together, they address Baldwin as a democratic theorist, activist, and citizen, examining his writings on the civil rights movement, religion, homosexuality, and women's rights. They investigate the ways in which his work speaks to and galvanizes a collective American polity, and explore his views on the political implications of individual experience in relation to race and gender. This volume not only considers Baldwin's works within their own historical context, but also applies the author's insights to recent events such as the Obama presidency and the Black Lives Matter movement, emphasizing his faith in the connections between the past and present. These incisive essays will encourage a new reading of Baldwin that celebrates his significant contributions to political and democratic theory."--Back cover.